Beyond Economic Calculus: Shared Islamic Identity as Deal Catalyst On Indonesia-Iran Preferential Trade Agreement - Athallah, Ilham Dary; Khairia, Hayara; Husna, Tsabita (UIN Sunan Ampel Surabaya, 2025)
This paper examines the Indonesia-Iran Preferential Trade Agreement (II-PTA), signed in May 2023 and ratified in late 2024, as a puzzle for traditional international political economy theories. This theory asserts that a country usually signs trade agreement because of their already significant economic interdependence. But those two Muslim majority nations recorded a relatively low volume in bilateral trade. Utilizing a constructivist framework, this study argues that shared Islamic identity played a significant role in shaping the national interests of both Indonesia and Iran, and driving the agreement forward beyond purely rational economic calculations. The analysis demonstrates how this shared identity, coupled with norms of solidarity within the Ummah, provided a powerful ideational foundation that not only defined cooperation as normatively appropriate but also facilitated the negotiation process. This research foregrounding Islamic identity as a central variable for economic cooperation that deviates from conventional market logic